2023
DOI: 10.3390/ijms241512152
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 1 Receptor (MC1R): Pharmacological and Therapeutic Aspects

Abstract: Melanocortins play crucial roles in regulating the stress response, inflammation, and skin pigmentation. In this review, we focus on the melanocortin 1 receptor (MC1R), a G protein-coupled receptor primarily known for regulating skin pigmentation and exhibiting anti-inflammatory effects. First, we provide an overview of the structure, signaling pathways, and related diseases of MC1R. Next, we discuss the potential therapeutic use of synthetic peptides and small molecule modulators of MC1R, highlighting the dev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…For example, Slominski et al [66], using in vitro and in vivo models, demonstrated that stimulation of melanogenesis leads to increased expression of HIF-1α and its subsequent translocation into the nucleus. Thus, it is possible that HIF-1α is induced by the production of intermediates of melanogenesis, including massive generation of reactive oxygen species [4,67,68]. Consequently, the initiation of melanogenesis affects the expression of multiple genes involved in regulating the behavior of melanocytes and melanoma cells, including the metabolic switch to glycolysis coordinated by HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Slominski et al [66], using in vitro and in vivo models, demonstrated that stimulation of melanogenesis leads to increased expression of HIF-1α and its subsequent translocation into the nucleus. Thus, it is possible that HIF-1α is induced by the production of intermediates of melanogenesis, including massive generation of reactive oxygen species [4,67,68]. Consequently, the initiation of melanogenesis affects the expression of multiple genes involved in regulating the behavior of melanocytes and melanoma cells, including the metabolic switch to glycolysis coordinated by HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…MC1R is a member of the melanocortin receptors (MCRs) subfamily, belonging to the G-protein-coupled receptors (GPCR). It has a high affinity for the α-MSH and its binding results in the production of darker eumelanin (García-Borrón et al, 2014;Mun et al, 2023). In contrast, ASIP competitively antagonizes α-MSH, and when it binds to MC1R, it stimulates the synthesis of the red or yellow phaeomelanin (Abdel-Malek et al, 1999).…”
Section: G Ene Ti C Ba S Is and Adap Tive E Voluti On Of S K In Colou...mentioning
confidence: 99%
“…Eumelanin produced by melanocytes is influenced by five known distinct melanocortin receptors. Dersimelagon has the highest affinity for the melanocortin-1 receptor (MC1R), a G-protein coupled receptor on melanocytes that binds to melanocortin to regulate skin and hair color (Table 3) [40][41][42]. MC1R is established as the main driver of human pigmentation [34].…”
Section: Mechanism Of Actionmentioning
confidence: 99%